2022
DOI: 10.1007/s12035-022-02830-6
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Social Stress Causes Sex- and Region-Dependent Dopaminergic Changes that Are Prevented by Minocycline

Abstract: Early life stress (ELS) is known to modify trajectories of brain dopaminergic development, but the mechanisms underlying have not been determined. ELS perturbs immune system and microglia reactivity, and inflammation and microglia influence dopaminergic transmission and development. Whether microglia mediate the effects of ELS on dopamine (DA) system development is still unknown. We explored the effects of repeated early social stress on development of the dopaminergic system in male and female mice through hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 118 publications
1
6
0
Order By: Relevance
“…This DAT1 gene�c data thus further corroborate the epigene�c ones, since HSP subjects, if repor�ng high levels of perceived stress, have higher levels of DAT1 DNA methyla�on, especially if carrying the 9/9 genotype, and higher expression of DAT1 miR-132. These molecular evidence could poten�ally drive lower DAT availability already reported at the preclinical level evoked by social stress (Catale et al, 2022) and at the clinical level for instance in major depression (Dubol et al, 2020;Meyer et al, 2001;Moriya et al, 2020;Pizzagalli et al, 2019). It is also relevant to point out that we did not observe any relevant change for the other gene under study, SERT, nor at the epigene�c levels when measuring DNA methyla�on and miRNAs expression nor at the gene�c levels when analyzing the 5-HTTLPR polymorphism.…”
Section: Discussionsupporting
confidence: 55%
“…This DAT1 gene�c data thus further corroborate the epigene�c ones, since HSP subjects, if repor�ng high levels of perceived stress, have higher levels of DAT1 DNA methyla�on, especially if carrying the 9/9 genotype, and higher expression of DAT1 miR-132. These molecular evidence could poten�ally drive lower DAT availability already reported at the preclinical level evoked by social stress (Catale et al, 2022) and at the clinical level for instance in major depression (Dubol et al, 2020;Meyer et al, 2001;Moriya et al, 2020;Pizzagalli et al, 2019). It is also relevant to point out that we did not observe any relevant change for the other gene under study, SERT, nor at the epigene�c levels when measuring DNA methyla�on and miRNAs expression nor at the gene�c levels when analyzing the 5-HTTLPR polymorphism.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, disruptions to neurotransmitter signaling and neuroendocrinology are implicated in both ELS and ASC. Preclinical studies have shown that chronic stress disrupts glutamate- (304)(305)(306)(307), serotonin- (308) and dopamine- (309)(310)(311)(312) signaling, leading to increased anxiety-like behaviors and impairments in social recognition, social interest and cognitive flexibility. These data are supported by human cohort studies showing that ELS disrupts dopaminergic responses to psychosocial stress (313,314), and alters glutamate/glutamine cycling (315) and serotonin transporter binding (316) in patients with MDD.…”
Section: Figurementioning
confidence: 99%
“…Importantly, the long-term effects of ELA may not be intractable. In preclinical research, some of the effects of ELA on dopaminergic circuits can be rescued by minocycline (Catale et al 2022). Further, susceptibility to morphine-induced conditioned place preference during adolescence can be mitigated by enriched maternal care during early development in a rodent model (Schwarz et al 2011).…”
Section: Early Life Adversity As An Elicitor and Moderator Of Inflamm...mentioning
confidence: 99%